apply1 : (a -> b) ->           Foo a ->     b
apply2 : (a -> b -> c) ->      Bar a b ->   c
apply3 : (a -> b -> c -> d) -> Baz a b c -> d

As you see there is a repeating pattern, we obtain a function and a data structure, then we apply that function and return its result...

Is it possible to abstract over this pattern with Pattern Calculus?

How would the definition for generic apply look like?


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Browse other questions tagged or ask your own question.